Diabetic nephropathy among type 2 diabetes mellitus patients in Dr. Cipto Mangunkusumo Hospital (Faculty of Medicine Universitas Indonesia, 2004)
Diabetic nephropathy has been known as one of the most serious long-term complications of diabetes mellitus (DM), which could lead to end-stage kidney failure. However, data showing the presence of diabetic nephropathy among ambulatory type 2 diabetic patients is currently not available. This cross-sectional study was conducted to find the prevalence of diabetic nephropathy among non-hospitalized type 2 diabetic patients, who came for the first time to the Metabolic and Endocrinology Clinic, Dr. Cipto Mangunkusumo Hospital, Jakarta. From December 2001 to June 2002, 100 new type 2 diabetic patients were included in the study. Forty-two of them were men and the mean age was 54 Â±Â 9.6 years. Overt nephropathy (macroalbuminuria) was found in 11% of patients, while incipient nephropathy (microalbuminuria) was 26%, and the rest were normal (normoalbuminuria). Duration of illness of more than 5 years was significantly correlated with the degree of albuminuria. However, there is no significant correlation between the degree of albuminuria and other risk factors, i.e. patientâs age, dyslipidemia, hypertension, obesity, HbA1c level. All patients with overt nephropathy had creatinine clearance test below 75 ml/ min. (mean 45.3 mL/min), significantly lower than patients with micro- or normoalbuminuria (p=0.01). Retinopathy was found in 10 out of 11 (90%) patients with overt nephropathy. Multivariate analysis showed that the duration of illness and retinopathy was significantly correlated with the presence of diabetic nephropathy (p< 0.05). We concluded that the prevalence of diabetic nephropathy (i.e. overt nephropathy with retinopathy) among non-hospitalized type 2 diabetic patients was 10%. The duration of illness was an important risk factor for the development of this complication. (Med J Indones 2004; 13: 161-5) Keywords: diabetic nephropathy, chronic kidney disease, diabetic retinopathy, albuminuria, ambulatory type 2 diabetic patients